2013
DOI: 10.1172/jci67615
|View full text |Cite
|
Sign up to set email alerts
|

Leptin regulation of Hsp60 impacts hypothalamic insulin signaling

Abstract: Type 2 diabetes is characterized by insulin resistance and mitochondrial dysfunction in classical target tissues such as muscle, fat, and liver. Using a murine model of type 2 diabetes, we show that there is hypothalamic insulin resistance and mitochondrial dysfunction due to downregulation of the mitochondrial chaperone HSP60. HSP60 reduction in obese, diabetic mice was due to a lack of proper leptin signaling and was restored by leptin treatment. Knockdown of Hsp60 in a mouse hypothalamic cell line mimicked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 72 publications
5
109
1
1
Order By: Relevance
“…This mitochondrial chaperonin is a ubiquitous molecule with multiple roles in health and disease [62,63] recently found to be involved in insulin resistance [62]. HSP60 appears to be modulated by leptin in the hypothalamus of obese and diabetic mice and decreased levels of leptin were found in accordance with the reduced presence of HSP60 [64]. Decreased levels of leptin, as mentioned above, were found correlated with the reduced presence of Hsp60.…”
Section: Discussionmentioning
confidence: 67%
“…This mitochondrial chaperonin is a ubiquitous molecule with multiple roles in health and disease [62,63] recently found to be involved in insulin resistance [62]. HSP60 appears to be modulated by leptin in the hypothalamus of obese and diabetic mice and decreased levels of leptin were found in accordance with the reduced presence of HSP60 [64]. Decreased levels of leptin, as mentioned above, were found correlated with the reduced presence of Hsp60.…”
Section: Discussionmentioning
confidence: 67%
“…It has been shown that insulin resistance in the brain (36), like insulin resistance in skeletal muscle (34), is associated with mitochondrial dysfunction, and mitochondrial dysfunction has been associated with neurological disorders (41). Examination of isolated mitochondria from brains of control and NIRKO mice using a Seahorse XF24 Extracellular Flux Analyzer revealed a 28 ± 9% reduction in basal oxygen consumption rate (OCR) compared with control (P < 0.05), even by 4 mo of age.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin resistance and type 2 diabetes are well documented to be associated with mitochondrial dysfunction in classical metabolic tissues, such as muscle (34) and liver (35), and we have recently demonstrated that obesity-induced insulin resistance is also associated with altered mitochondrial function in the hypothalamus (36). Patients with major depression have also been shown to exhibit mitochondrial dysfunction in the brain (37).…”
mentioning
confidence: 87%
“…There are other aspects of mitochondrial biology that are linked to insulin resistance, such as mitochondrial quality control (151,152), fission/fusion (153) and proteostasis (154), and reviewed in (155)) that are also regulated by ROS production (reviewed in (156)). …”
mentioning
confidence: 99%